Black hole entropy without microstates. (1st April 2019) - Garfinkle, David
Abstract: I argue that black hole area should be thought of as an 'entropy-like quantity' rather than an entropy. This precludes the need for a statistical mechanical description of black hole thermodynamics in terms of microstates.